Food Composition in The Stomach of Selais Bungkuk (Hemisilurus heterorhynchus) in The Kampar Kiri River, Mentulik Village, Riau Province - Roza Elvyra; Nurul Hakiki; Yusfiati Yusfiati; Khairijon Khairijon; Imelda Wardani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Food Composition in The Stomach of Selais Bungkuk (Hemisilurus heterorhynchus) in The Kampar Kiri River, Mentulik Village, Riau Province